The meanings of Imperative Structures in the Rules of Fundamentalism - Esmail, Amani Ali (Journal of Islamic Sciences, 2023)
Words have a close relationship with the meanings, there is no doubt that a verb is a basic element in building sentences and words as it has a great and importance, most of all is imperative verb. That importance stems from the obligations and duties that result from it, and therefore this study aims to explain the meaning of the imperative verbs and what results from the obligatory structure because it is issued by Allah; and to include some of the evidence that imperative’s meaning is changed from the obligation to other meanings. This study also mentions the opinions of scholars on some issues of the rule of imperative structures with obligatory meaning, and then some applications on the rule, because imperative structure has an effect on Allah commands are abided by.
Keywords: meaning of imperative; obligatory meaning of imperative; evidence that change the meaning of imperative to other meanings; Fundamentals of Islamic jurisprudence